Externalities of business entities from plastic pollution at Perhentian island, Malaysia - Sarah Tan Yen Ling, Hanim Kamaruddin,; Hoe, Loh Ing (Opción)
Marine protected areas have been formed by the government of Malaysia to conserve and protect marine environment from human interference and distinction. However, the establishment of business entities in marine protected areas has caused pollution to marine environment. This article identified the type of pollutants contributed by business entities located in Long Beach, Perhentian Island, Malaysia to its marine environment. A mixed method of research has been adopted in this study involving fieldwork and interviews with business entities located in the coastal area of Long Beach. Results indicate that plastic products are the main type of pollutants in Long Beach. Effective measures have to be taken in order to sustain the development of Long Beach, Perhentian Island.